Using cognitive task analysis to identify critical decisions in the laparoscopic environment. - Craig, Curtis; Klein, Martina I; Griswold, John; Gaitonde, Krishnanath; McGill, Thomas; Halldorsson, Ari (Human Factors, 2012)
Objective: The aim of this study was to identify the critical decisions surgeons need to make regarding laparoscopic surgery, the information these decisions are based on, the strategies employed by surgeons to reach their objectives, and the difficulties experienced by novices.Background: Laparoscopic training focuses on the development of technical skills. However, successful surgical outcomes are also dependent on appropriate decisions made during surgery, which are influenced by critical cues and the use of appropriate strategies. Novices might not be as adept at cue detection and strategy use.Method: Participants were eight attending surgeons. The authors employed task-analytic techniques to identify critical decisions inherent in laparoscopy and the cues, strategies, and novice traps associated with these decisions.Results: The authors used decision requirements tables to organize the data into the key decisions made during the preoperative, operative, and postoperative phases as well as the cues, strategies, and novice traps associated with these decisions. Key decisions identified for the preoperative phase included but were not limited to the decision of performing a laparoscopic versus open surgery, necessity to review the literature, practicing the procedure, and trocar placement. Some key decisions identified for the operative phase included converting to open surgery, performing angiograms, cutting tissue or organs, and reevaluation of the approach. Only one key decision was identified for the postoperative phrase: whether the surgeon's technique needs to be evaluated and revised.Conclusion: The laparoscopic environment requires complex decision making, and novices are prone to errors in their decisions.Application: The information elicited in this study is applicable to laparoscopic training.